Food Security Ensurance in Vietnam Today - Dung, Pham Van (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
Today, food security and national food secuirty ensurance should be viewed from the perspetive of the market economy and the international integration because these constantly changing contexts have significant impacts on those issues. After over 30 years of innovation, though the State has addressed the food secuirty related issues effectively, Vietnam is still facing with enormous challenges and instabilities. Therefore, Vietnam should consider and amend food production and export activities in size and quality; build mechanism, policy to facilitate paddy farmers,... The State has to ensure food security while it should satisfy the market’s requirements, ensure income of paddy farmers, and needs of food enterprises. Keywords Food security, market economy, integration, Vietnam References [1] Chính phủ, Nghị quyết về đảm bảo an ninh lương thực quốc gia, Hà Nội, ngày 23/12/2009. [2] Tạ Ngọc Tấn, An ninh quốc gia - Những vấn đề an ninh phi truyền thống, NXB. Chính trị - Hành chính, Hà Nội, 2013. [3] Tổng cục Thống kê, Niên giám thống kê năm 2016, NXB. Thống kê, Hà Nội, 2017. [4] Lê Hùng, “Dân số thế giới sẽ đạt hơn 11 tỷ người vào cuối thế kỷ”, đăng tải ngày 13/8/2015, Vnexpress, http://vnexpress.net/tin-tuc/khoa-hoc/dan-so-the-gioi-se-dat-hon-11-ty-nguoi-vao-cuoi-the-ky-3263225.html [5] Nguyễn Hoàng, “Tình trạng nông dân bỏ ruộng ngày càng tăng”, đăng tải ngày 20/7/2016, Hội Nông dân Việt Nam, http://tnnn.hoinongdan.org.vn/sitepages/news/1093/45366/tinh-trang-nong-dan-bo-ruong-ngay-cang-tang [6] Bạch Dương, “Báo động gạo Việt sang Mỹ bị trả về”, đăng tải ngày 3/10/2016, VnEconomy, http://vneconomy.vn/thi-truong/bao-dong-gao-viet-sang-my-bi-tra-ve-2016100210284730.htm